Vitamin, antioxidant and micronutrient supplementation and the risk of developing incident autoimmune diseases: a systematic review and meta-analysis - Low, Chen Ee; Loke, Sean; Chew, Nicole Shi Min; Lee, Ainsley Ryan Yan Bin; Tay, Sen Hee (Frontiers in Immunology, 2024)
BackgroundAutoimmune diseases pose significant health challenges worldwide and affect millions. In recent years, there has been growing interest in exploring preventive strategies through nutritional interventions using vitamins, antioxidants, and micronutrients to reduce the risk of developing autoimmune diseases. However, excessive supplementation has also been associated with toxicity.ObjectiveWe aim to assess how the intake of vitamins, antioxidants and micronutrients affect the risk of developing autoimmune diseases.MethodsThis PRISMA-adherent systematic review involved a systematic search of PubMed, Embase and Cochrane for controlled studies that evaluated the risk of incident autoimmune diseases after supplementation. Random effects meta-analyses were used for primary analysis.Results18 studies were included. Overall meta-analyses observed that vitamin D did not influence the risk of autoimmune diseases (RR=0.99, 95%CI: 0.81-1.20). However, among the different vitamin D dosages, subgroup analysis demonstrated that those who were supplemented with 600-800IU/day may have a statistically significant reduction in risk (RR=0.55, 95%CI: 0.38; 0.82). Systematic review suggested that consumption of most vitamins, micronutrients and antioxidants may not have any effect on the risk of autoimmune diseases. Smoking, age, physical or outdoor activity and diet were significant confounding factors that affected the efficacy of such interventions.ConclusionWe studied the effect of various vitamins, micronutrients and antioxidants on the risk of developing autoimmune diseases. Our study contributes to the evolving landscape of nutritional immunology, providing a foundation for future research to unravel more definite relationships with supplementation and the development of incident autoimmune diseases.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024504796.